The correlation between trauma and poor diet in oral ulceration: an online-based survey - Nanan Nur'aeny; Dida Akhmad Gurnida; Dzulfikar Djalil Lukmanul Hakim; Fransisca Sri Susilaningsih; Dewi Marhaeni Diah Herawati (Majalah Kedokteran Gigi Indonesia, 2020)
The most common oral ulceration in the community might be as recurrent as aphthous stomatitis (RAS) or traumatic ulcer. The aim of this study was to report and analyze the characteristics of oral ulceration and risk factors based on an online survey. A questionnaire using Google forms containing a total of 34 questions. Four questions wereabout personal details, whereas 30 questions related to oral ulceration were recorded and presented descriptively. The chi square test was carried out to determine the relationship between several questionnaire variables. A total of 208 respondents were involved, consisting of 162 female and 46 male. Respondents were in the age range of 0–50 year old with >23 year old as the age group with the highest number of respondents (53%). Oral ulceration data showed no recurrence in 157 respondents (75%), rare recurrence/ once in a year (52%), frequent recurrence in the labial mucosa in 121 respondents, single ulcer (86%), round shape (75%), risk factor due to trauma (biting/friction) in 165 respondents, ulcer untreated (64 %), and ulcer recovery of less than 7 days (70%). The respondents had no symptoms of anemia (73%), and were not on a vegan diet (98%). Chi square test indicated that there was a significant correlation between trauma and the poor diet (p= 0.001). The data in this present study indicate that the characteristics of oral ulceration might lead to RAS or traumatic ulcers and this might be attributed to local (trauma) and systemic (diet) factors.